Literature Study: Burnout and Coping among Emergency Room Nurses - Ivana Sundari; Kurniawan Yudianto; Aan Nuraeni (Universitas Padjadjaran, 2022)
Burnout is an emotional fatigue syndrome that often occurs on nurses in Emergency Department (ED). Emergency room nurses provide care quickly, responsively, and precisely. One of the factors that influence the burnout level is coping. Previous theories have not been able to explain positive coping for nurses who experience burnout, as well as literature review concerning burnout and coping among emergency room nurses are still minimal, so further research is needed. This study aims to identify burnout and coping among emergency room nurses. This research is a narrative review. Conduct search for research articles in the CINAHL, Pubmed, Science Direct, and Google Scholar databases using